Advancing English Language Teaching through Survey Research: Methodologies, Impacts and Applications - Pandey , Gopal Prasad (Nepal Journal of Multidisciplinary Research, 2024)
Background: A survey is a tool used to gather data that describes one or more attributes of a particular group. This tool, as a research design concentrates on examining the attitudes, opinions, and characteristics of a particular group. Survey research design in English Language Teaching (ELT) involves using questionnaires or interviews to collect data from a sample of participants to generalize findings about larger populations. Methods: This article comprehensively explores the use and methodologies of survey research within various academic fields, particularly emphasizing its impact on English Language Teaching (ELT). The paper explores the methodical process of gathering and analyzing data, emphasizing how surveys are used to record a wide range of viewpoints on teaching methods, learner opinions, and educational results. Results: This design is commonly used in ELT and applied linguistics research to gather information on language learning strategies, teacher attitudes, student satisfaction, or the effectiveness of teaching methods. This data assists educators and administrators in making well-informed choices about the development of curriculum, training of teachers, and allocation of resources. Conclusion: The paper describes the primary methods, techniques, and tools used in survey research design. Moreover, the paper provides an outline for survey research that English teachers can utilize in the classroom. Novelty: Survey research in ELT captures diverse data on teaching methods, learner achievements, and educational contexts. It facilitates large-scale data collection, enabling generalization of findings, and investigates correlations between teaching practices and student outcomes.